(untitled) (International Journal of Engineering Management Science, 2022)
This paper presents a new high step-up dc/dc converter for renewable energy systems in which a high voltage gain is provided by using a coupled inductor. The operation of the proposed converter is based on a charging capacitor with a single power switch in its structure. A passive clamp circuit composed of capacitors and diodes is employed in the proposed converter for lowering the voltage stress on the power switch as well as increasing the voltage gain of the converter. Since the voltage stress is low in the provided topology, a switch with a small ON-state resistance can be used. As a result, the losses are decreased and the efficiency is increased. Therefore, a main power switch with low resistance RDS (ON)can be used to reduce the conduction losses. The operation principle and the steady-state analyses are discussed thoroughly. To verify the performance of the presented converter, a 300W laboratory prototype circuit is implemented. The results validate the theoretical analyses and the practicability of the presented high step-up converter